Maximising D − T fusion power by optimising the plasma composition and beam choice in JET. (1st May 2022) - Van Eester, D; Lerche, E; Huynh, P; Johnson, T; Yadikin, D; Štancar, Ž; Aleiferis, S; Frigione, D; Garzotti, L; Lomas, P; Lowry, C; Maslov, M; et al.
Abstract: JET has a neutral beam injection as well as a radio frequency (RF) system for bringing plasmas to fusion-relevant temperatures. The former allows D as well as T birth energies of the order of 100–120 keV while the latter has the flexibility to heat a variety of populations by adjusting the antenna frequency. In this paper it is illustrated that—when the JET plasma is heated—the power harvested from D  −  T fusion reactions favours operating away from the 50–50 D  −  T balance and that exploiting pure D beams is more beneficial than combined D and T beams as well as pure T beams. Although beam heating dominates the overall behaviour in JET—as much more beam power than wave power can be coupled to the plasma—RF heating allows efficient heating of the very core.